The New Left in the European Democracies: The Case of the German Radical Left - Marco Damiani (Coordinamento SIBA, 2015)
The new form of the social and political conflict cannot be explained by the traditional categories of right and left, but it articulates to them on two plans, that of the establishment, intended like plan of the structured political conflict from the traditional actors, and that of the anti-establishment, in which new representations of politics emerge. The New Left is characterized by type of intermittent participation and new perspectives on mobilization inside the parties and the social movements. This type of parties differs moreover from the traditional ones left of the socialist and social democratic left in not arranging of organizations collaterals placed under the direction of the leadership of the same party. The mobilization that spontaneously assumes not conventional forms of active participation of the citizens, or is primed by the action of an associative network of which the same parties take part, than however does not monopo-lize the collective action. In this regard, the attention will be dedicated to the study of Die Linke: an anti-establishment party of the non-socialist German left-wing, heir to the communist tradition. The choice was affected to the German model because: 1) Germany is a country with a strong social democratic tradition, but 25 years after the fall of the Berlin Wall the German political system identifies a new antagonist political party; 2) Die Linke represents an interesting case in the political landscape of the European radical left because is a one-party that gives up at the federation of parties to try to unify the political parties of German radical left-wing.